(Effect of Temperature and Concentration of Sodium Hidroxida Producing Activated Carbon From Paddy Husk) - Pohan, H.G; Siallagan, Christiana; Wulandari, Rianti (Balai Besar Industri Agro, 1994)
Production of activated carbon from paddy husk has been conducted with activation temperature and refluxed by NaOH (at 50-60 degree C. The activation temperature are 600; 800; and 1000 degree C with the concentration of NaOH 5;10;and 15%.The result is treated with activation temperature 800 degree C with 15% NaOH. The result has adsoption ability 514,36 mg/gr.From the analysis result of bond funcation showed that the activated carbon act as carbon-H (carbon with alkaline bond function).